2014
DOI: 10.1063/1.4861184
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of fullerenol C60(OH)10/Au interface

Abstract: Electrical properties of the C60(OH)10/Au contact have been studied by measuring its current-voltage characteristics in the temperature range of 300–500 K. The Schottky barrier of the C60(OH)10/Au contact was confirmed to be 0.70±0.02 eV from Arrhenius plots of the current-voltage characteristics measured at various bias voltages as well as various preparation conditions of the C60(OH)10 material. Significant effect of the applied electric field on the barrier height has not been observed in the range of 0.1–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…% was purchased from LUNA Innovations to make a sample specimen for measurement. 18,19 The Er 3 N@C 80 powder was pressed into a pellet at room temperature at 1.25 GPa for 50 min. The so formed pellet was 5.0 mm in diameter and 0.55 mm in thickness.…”
Section: Methodsmentioning
confidence: 99%
“…% was purchased from LUNA Innovations to make a sample specimen for measurement. 18,19 The Er 3 N@C 80 powder was pressed into a pellet at room temperature at 1.25 GPa for 50 min. The so formed pellet was 5.0 mm in diameter and 0.55 mm in thickness.…”
Section: Methodsmentioning
confidence: 99%
“…In previous works [11], we have reported that Schottky barrier of the C 60 (OH) 10 /Au contact was 0.70 ± 0.02 eV and no significant effect of the applied electric field was observed on the barrier height.…”
Section: Introductionmentioning
confidence: 75%
“…On the contrary, fullerenol [C 60 (OH)] displayed amorphous characteristics, indicated by a broad hump at a 2 θ value of around 32° in the X‐ray diffraction (XRD) pattern (Figure 1c). The crystallinity of C 60 (OH) is very poor compared to that of fullerenes [21,22] . Interestingly, the initially poor crystallinity transformed into a highly crystalline material upon pyrolysis at 600 °C, as shown by the sharp and intense diffraction patterns (Figure 1c).…”
Section: Resultsmentioning
confidence: 98%
“…The crystallinity of C 60 (OH) is very poor compared to that of fullerenes. [21,22] Interestingly, the initially poor crystallinity transformed into a highly crystalline material upon pyrolysis at 600 °C, as shown by the sharp and intense diffraction patterns (Figure 1c). Pyrolyzing fullerenol at 900 °C caused structural degradation where almost no functional group was detected through Fourier-transform infrared (FTIR) spectroscopy (Figures S3 and S4).…”
Section: Resultsmentioning
confidence: 98%